ANALISIS MELODI VOKAL BELENGGANG DALAM UPACARA BAYAR NIAT PADA MASYARAKAT DAYAK BELANGIN DI DESA PAKURAYA KECAMATAN KUALA BEHE KABUPATEN LANDAK - Jesica Yosepina Echi; Yudhistira Oscar Olendo; Asfar Muniir (Universitas Tanjungpura, 2021)
AbstractThis research is motivated by the lack of interest of the younger generation in the traditional arts which are a hereditary heritage of ancestors and the need for efforts to study and preserve the traditional of music. One of the traditional arts that is almost extint and began to be unknown by the people themselves the purpose of this thesis is to describe. Analysis of the Vocal Melody in the Ceremony of Paying Intetions in the Belangin Dayak Community in PakuRaya Village, Kuala Behe District, Landak Regency. The method used is descriptive method with a qualitative form through ethnomusicology approach. The research data are (1) Shackles Vocal Performance in the Intention of Paying Rituals (2) Belenggang Vocal Instruments (3) Analysis of Shackles Vocal themes, motifs, bars, scale, notes, tempo, dynamics, and phrases. The results of the study are: 1) There is a technique in bringing the Vocal Shackles and the meaning of the words 2) Ringing Vocal Notation, using musical notes in the form of sheet music.Keywords: Pay Intention, Vocal Shackles, Vocal Instruments